An investigation into fatigue behaviour and damage progression in pseudo-ductile thin-ply angle-ply laminates. (October 2021) - Wu, X.; Fuller, J.D.; Wisnom, M.R.
Abstract: This paper presents a detailed investigation on the fatigue response and damage progression in pseudo-ductile thin-ply angle-ply laminates with two configurations: an intermediate modulus-high modulus fibre combined IM-HM [±277 /0]s and a standard modulus SM-SM [±266 /0]s laminate. 80% of the "yield" stress was found to be the maximum stress for both laminates, where they can withstand 10 6 cycles without obvious damage or stiffness reduction. When laminates containing pre-fractured 0° plies were loaded in fatigue, both of the laminates showed a delamination dominated damage mode: the delamination initiated from the pre-fractured 0° plies and propagated at the interface between the 0° and angle plies with increasing number of cycles. An estimated delamination growth rate based on the stiffness reduction and delamination initiated from 0° ply fracture are also discussed. The IM-HM laminate with broken 0° fibres can still withstand fatigue loading at 80% severity without further modulus reduction or damage progression, whilst the SM-SM failed in delamination within a small number of cycles.